Study of the B-→Λ+cΛ[bar]-cK- decay - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Physical review, 2023)
The decay B−→Λ+c¯Λ−cK− is studied in proton-proton collisions at a center-of-mass energy of √s=13 TeV using data corresponding to an integrated luminosity of 5 fb−1 collected by the LHCb experiment. In the Λ+cK− system, the Ξc(2930)0 state observed at the BABAR and Belle experiments is resolved into two narrower states, Ξc(2923)0 and Ξc(2939)0, whose masses and widths are measured to be m(Ξc(2923)0)=2924.5±0.4±1.1 MeV, m(Ξc(2939)0)=2938.5±0.9±2.3 MeV, Γ(Ξc(2923)0)=4.8±0.9±1.5 MeV, Γ(Ξc(2939)0)=11.0±1.9±7.5 MeV, where the first uncertainties are statistical and the second systematic. The results are consistent with a previous LHCb measurement using a prompt Λ+cK− sample. Evidence of a new Ξc(2880)0 state is found with a local significance of 3.8σ, whose mass and width are measured to be 2881.8±3.1±8.5 MeV and 12.4±5.3±5.8 MeV, respectively. In addition, evidence of a new decay mode Ξc(2790)0→Λ+cK− is found with a significance of 3.7σ. The relative branching fraction of B−→Λ+c¯Λ−cK− with respect to the B−→D+D−K− decay is measured to be 2.36±0.11±0.22±0.25, where the first uncertainty is statistical, the second systematic and the third originates from the branching fractions of charm hadron decays.13.05.2024